2014
DOI: 10.1021/nn405627s
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Force-Driven, Large-Area Alignment of Multi-segmented Nanowires

Abstract: Capillary force-driven, large-area alignment of multi-segmented nanowires," ACM Nano, v. 8, no.2 (2014) pp. 1511-1516.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 43 publications
1
92
0
Order By: Relevance
“…127 Capillary forces have also been used by Mirkin et al to achieve shape selectivity during the self-assembly process, 128 and to place segmented nanowires in well-defined bidimensional arrays. 129 Despite the growing understanding of fundamental principles of capillary forces in confined nanostructures, the methods proposed for capilarity-driven self-assembly of NPs are often specific for the systems studied. Combining nanofabricated surfaces with capilary forces requires delicate tuning of several experimental variables, and allows precise control of the positioning of NPs after considerable experimental effort.…”
Section: Template Driven Self-assembly Of Nps At Interfaces and Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…127 Capillary forces have also been used by Mirkin et al to achieve shape selectivity during the self-assembly process, 128 and to place segmented nanowires in well-defined bidimensional arrays. 129 Despite the growing understanding of fundamental principles of capillary forces in confined nanostructures, the methods proposed for capilarity-driven self-assembly of NPs are often specific for the systems studied. Combining nanofabricated surfaces with capilary forces requires delicate tuning of several experimental variables, and allows precise control of the positioning of NPs after considerable experimental effort.…”
Section: Template Driven Self-assembly Of Nps At Interfaces and Surfacesmentioning
confidence: 99%
“…137 Capilary forces, discussed in the previous section, have been combined with top-down nanofabricated templates to control orientation and positiong of NPs on surfaces. 106,107,[116][117][118][119][120][121][122][123][124][125][126][127][128][129] Selective chemical functionalization of surfaces has also been used to drive the self-assembly of NPs exploiting the chemistry of silane-derivatives on Si surfaces [138][139][140] and using micro-contact printing on gold surfaces. 141 Direct surface self-assembly methods are versatile and allow the development of more advanced procedures to increase the control of nanostructure positioning and topographical orientation of small objects.…”
Section: Template Driven Self-assembly Of Nps At Interfaces and Surfacesmentioning
confidence: 99%
“…Thus, it is required to control the displacement of 1D nanostrcutres into hierarchically ordered structures in large area. Within the past decades, many researches have reported various methods including spin-coating, 6 molecular interaction, 7,8 LangmuirBlodgett (LB) method, [9][10][11] microfluidic channel, 12 electric field, 13 magnetic field, 14 micro-contact stamping, 15,16 and template-assisted assembly [17][18][19][20][21] in order to control the alignment and positioning of the 1D nanostructures in large area. The template-assisted assembly utilizing chemically or topographically patterned surfaces as templates among those methods has been frequently concerned as an effective way to produce the large-scale assembly of 1D nanostructures since they can be deposited on desired sites by guidance of the templates during evaporation of suspending solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In general, such assembling processes of nanowires can be performed at relatively low temperatures1234567891011121314151617181920212223242526, which are much lower than typical nanowire growth temperatures272829303132. Therefore, this assembling method allows us to integrate single crystalline nanowires, which are grown at relatively high temperatures, on various substrates via low temperature processes.…”
mentioning
confidence: 99%
“…Such integration of heterogeneous single crystalline objects on the same substrate is rather difficult to be accomplished via conventional growth and lithography techniques. Previous studies have demonstrated that nanowires dispersed in solution can be aligned on the substrate by electric field12, magnetic field345, fluid flow678, capillary force91011123334, oil/water interface1314 and others151617181920212235. Among them, methods using lithographically defined patterns are promising for assembling heterogeneous nanowires due to the spatial controllability of patterns1011123335.…”
mentioning
confidence: 99%